Insights into the pathogenesis of GvHD: what mice can teach us about man. Issue 1 (23rd December 2014) - Hülsdünker, J.; Zeiser, R.
Abstract Acute graft‐vs‐host disease (GvHD) is a life‐threatening complication of allogeneic hematopoietic cell transplantation (allo‐HCT). Most of the knowledge about the biology of GvHD is derived from mouse models of this disease and therefore a critical analysis of potential advantages and disadvantages of the murine GvHD models is important to classify and understand the findings made in these models. The central events leading up to GvHD were characterized in three phases which includes the tissue damage‐phase, the T cell priming‐phase and the effector‐phase, when the disease becomes clinically overt. The role of individual cytokines, chemokines, transcription factor or receptors was studied in these models by using gene deficient or transgenic mice in the donor or recipient compartments. Besides, numerous studies have been performed in these models to prevent or treat GvHD. Several recent clinical trials were all based on previously reported findings from the mouse model of GvHD such as the trials on CCR5‐blockade, donor statin treatment, vorinostat treatment or adoptive transfer of regulatory T cells for GvHD prevention. The different mouse models for GvHD and graft‐vs‐leukemia effects are critically reviewed and their impact on current clinical practice is discussed.